Efektifitas Penggunaan Misoprostol Dan Oksitosin Pada Penanganan Perdarahan Post Partum Di BPM Suryati Bekasi - Suryati Regen; Tuty Yanuarti (Malahayati Nursing Journal, 2022)
ABSTRACT According to the World Health Organization (WHO), death is defined as death that occurs during pregnancy or within 42 days of delivery. The World Health Organization (WHO) in 2020, said as many as 295,000 women worldwide lost their lives during and after childbirth and childbirth. Based on data obtained at BPM Suryati from January to June 2021, there were 20 maternity mothers who experienced postpartum hemorrhage from 62 deliveries. A preliminary study conducted by researchers at BPM in September 2021 showed 12 mothers giving birth and 4 people experiencing postpartum hemorrhage. From the data above, there are still many pregnant women who experience postpartum hemorrhage, with proper management to avoid complications and death in postpartum mothers. It is known the average post partum bleeding before and after the use of misoprostol and oxytocin and analyzing the effectiveness of the use of misoprostol and oxytocin in the treatment of postpartum hemorrhage at BPM Suryati Bekasi in 2021. Quasi experimental with one group pretest-posttest design. Quasi-experimental research is a form of experimental research that does not have a control group (Notoatmodjo, 2018). The average post-partum bleeding before being given misoprostol and oxytocin to women giving birth at BPM Suryati Bekasi for the period October-December 2021 was 403.25 and the average post-partum bleeding after being given misoprostol and oxytocin to women giving birth at BPM Suryati Bekasi for the period October-December 2021 is 140.25. There is an effectiveness of using misoprostol and oxytocin on postpartum hemorrhage at BPM Suryati Bekasi for the period October-December 2021. Keywords : Post partum, Misoprostol and Oxytocin ABSTRAK Menurut Organisasi Kesehatan Dunia atau World Health Organization (WHO), kematian ibu didefinisikan sebagai kematian yang terjadi saat masa kehamilan atau dalam kurun waktu 42 hari setelah persalinan. World Health Organization (WHO) tahun 2020, menyebutkan sebanyak 295.000 wanita di seluruh dunia kehilangan nyawa mereka selama dan setelah kehamilan dan melahirkan. Berdasarkan data yang didapatkan di BPM Suryati  dari bulan Januari Juni 2021 terdapat 20 orang ibu bersalin mengalami perdarahan post partum dari 62 persalinan. Studi pendahuluan yang telah dilakukan oleh peneliti di BPM pada bulan September 2021 terdapat 12 ibu bersalin dan yang mengalami perdarahan post partum ada 4 orang. Dari data diatas terlihat ibu bersalin masih banyak yang mengalami perdarahan post pastum, dengan demikian penatalaksanaanya harus tepat supaya tidak terjadi komplikasi dan kematian pada ibu post partum. Diketahui rata-rata perdarahan post partum sebelum dan sesudah penggunaan misoprostol dan oksitosin dan menganalisis efektivitas penggunaan misoprostol dan oksitosin pada penanganan perdarahan post prtum di BPM Suryati Bekasi tahun 2021. Quasi eksperimental dengan rancangan one group pretest-posttest design. Penelitian quasi eksperimental merupakan salah satu bentuk penelitian eksperimental yang tidak memiliki control grup (Notoatmodjo, 2018). Rata-rata perdarahan post partum sebelum diberikan misoprostol dan oksitosin pada ibu bersalin di BPM Suryati Bekasi periode Oktober-Desember 2021 sebesar 403,25 dan rata-rata perdarahan post partum sesudah diberikan misoprostol dan oksitosin pada ibu bersalin di BPM Suryati Bekasi periode Oktober-Desember 2021 sebesar 140,25. Ada efektivitas penggunaan misoprostol dan oksitosin pada perdarahan post partum di BPM Suryati Bekasi periode Oktober-Desember 2021. Kata kunci: Post partum, Misoprostol, dan Oksitosin